2020
DOI: 10.1016/j.ssmph.2020.100621
|View full text |Cite
|
Sign up to set email alerts
|

Associations between village-level norms on marital age and marital choice outcomes among adolescent wives in rural Niger

Abstract: Social norms, the often unspoken rules that dictate behavior, are increasingly understood to play a role in child, early and forced marriage (CEFM) practices, but are less frequently examined in quantitative research on CEFM. No research on this topic has focused on Niger, despite the country having the highest prevalence of child marriage in the world. This study examines the associations of community and individual-level norms on marital age and marital choice with the outcomes of girls' age at marriage and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Based on the importance of women’s age and parity in reproductive autonomy and IPV [ 5 , 7 , 14 ], as well as prior associations in this population [ 17 ], we also conducted baseline age- and baseline parity-stratified post-hoc analyses for primary and secondary outcome; these models were minimally adjusted as a result of small cell sizes. We conducted an additional post-hoc sensitivity analysis utilizing inverse probability of censoring (IPC) weighting to account for the influence of greater loss to follow-up in some groups.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the importance of women’s age and parity in reproductive autonomy and IPV [ 5 , 7 , 14 ], as well as prior associations in this population [ 17 ], we also conducted baseline age- and baseline parity-stratified post-hoc analyses for primary and secondary outcome; these models were minimally adjusted as a result of small cell sizes. We conducted an additional post-hoc sensitivity analysis utilizing inverse probability of censoring (IPC) weighting to account for the influence of greater loss to follow-up in some groups.…”
Section: Methodsmentioning
confidence: 99%
“…Early marriage has been linked to multiple adverse health outcomes (e.g., maternal and infant mortality), many of which stem from early childbearing [ 3 , 4 ]. Social norms support early childbearing in Niger [ 5 ], with a median age at first birth of 18.2 for rural-residing women [ 1 ]. This early childbearing is experienced in tandem with low contraceptive prevalence, with fewer than 6% of married 15–19 year old girls using modern contraception, contributing to the highest levels of fertility in the world for adolescent Nigerien girls [ 1 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, evidence from a panel study in Nepal showed that collective beliefs about ideal marriage age and positive attitudes toward remaining single among neighbors are negatively associated with the likelihood of first marriage over a period of 4 years (Yabiku, 2006). Similarly, a recent study on rural Niger found that village level norms related to marriage age and support for marital choice influence the likelihood of adolescent girls marrying early (Shakya et al, 2020). In southern Malawi, Steinhaus et al (2019) examined marriage norms using social norm theory (Bicchieri, 2016), more explicitly attempting to evaluate whether child marriage can be defined as a social norm.…”
Section: Social Norm Theorymentioning
confidence: 99%
“…In Niger specifically, studies have examined the influence of gender norms and gender inequality on early child and forced marriage [21] and FP use [22,23]. In the Maradi region of Niger, women were more likely to use modern contraception if they had discussed contraceptive use with their husband [23].…”
Section: Introductionmentioning
confidence: 99%